Teaching English in Early Childhood Education: a Description of the Pedagogical Practice Adopted in the Municipality of Southern Brazil - Fernanda Seidel Bortolotti; Cibele Krause-Lemke (Educational Challenges, 2021)
The purpose of this study is to investigate teaching English in Early Childhood Education (ECE) in a municipality of southern Brazil. The country has not agreed to make English language teaching compulsory for this age, but some private schools have introduced English language teaching on the premises .